UPAYA MENCETAK LULUSAN YANG UNGGUL DAN BERMORAL : INTEGRASI IMTAQ DAN IPTEK DI SMKS MAMBAUL ULUM BATA-BATA PAMEKASAN MADURA - Hakim, Lukman (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
The formation of student character is currently very important, especially in creating superior and moral graduates to help a better generation of the nation. The research method is a qualitative approach with a descriptive type. The purpose of the study is to determine the efforts made at SMKS Mambaul Ulum Bata-Bata Pamekasan Madura in creating superior and moral graduates with informant sources such as the principal, vice principal, productive, normative and biblical teachers, active students, alumni, public relations, and BKK managers. The results of the study indicate that: 1) Implementation of eight national education standards, namely; content standards, process standards, graduate competency standards, education and education personnel standards, facilities and infrastructure standards, management standards, financing standards, and education assessment standards. 2) The impact of the integration of IMTAQ and IMTEK, namely; the existence of a strong religious culture through guidance and understanding of Islam such as ethical procedures, behavior, and having morality in accordance with the motto of the Mambaul Ulum Bata-Bata Islamic Boarding School. The importance of strengthening students' character must be truly considered in order to form a superior, responsible, and integrity generation to face global challenges by implementing IMTAQ and IMTEK in schools.